A murine oral model for Mycobacterium avium subsp. paratuberculosis infection and immunomodulation with Lactobacillus casei ATCC 334 - Cooney, Meagan A.; Steele, James L.; Steinberg, Howard; Talaat, Adel M. (Frontiers in Cellular and Infection Microbiology, 2014)
Mycobacterium avium subsp. paratuberculosis (M. paratuberculosis) the causative agent of Johne’s disease, is one of the most serious infectious diseases in dairy cattle worldwide. Due to the chronic nature of this disease and no feasible control strategy, it is essential to have an efficient animal model which is representative of the natural route of infection as well as a viable treatment option. In this report, we evaluated the effect of different doses of M. paratuberculosis in their ability to colonize murine tissues following oral delivery and the ability of Lactobacillus casei ATCC 334, a nascent probiotic, to combat paratuberculosis. Oral inoculation of mice was able to establish paratuberculosis in a dose-dependent manner. Two consecutive doses of approximately 109 CFU per mouse resulted in a disseminated infection, whereas lower doses were not efficient to establish infection. All inoculated mice were colonized with M. paratuberculosis, maintained infection for up to 24 weeks post infection and generated immune responses that reflect M. paratuberculosis infection in cattle. Notably, oral administration of L. casei ATCC 334 did not reduce the level of M. paratuberculosis colonization in treated animals. Interestingly, cytokine responses and histology indicated a trend for the immunomodulation and reduction of pathology in animals receiving L. casei ATCC 334 treatment. Overall, a reproducible oral model of paratuberculosis in mice was established that could be used for future vaccine experiments. Although the L. casei ATCC 334 was not a promising candidate for controlling paratuberculosis, we established a protocol to screen other probiotic candidates.